同性愛先天性初探: Preliminary Approach to Innateness of Homosexuality - WAN, Yan-Hai; ER, Yan (International Journal of Chinese & Comparative Philosophy of Medicine, 1998)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文討論了關於同性愛是先天形成還是後天形成的爭論，介紹了近年來有關同性愛與腦部結構相關性的研究結果，這些結果在一定程度上支持了同性愛先天性的論點，討論了對這些研究結果的爭議，以及同性愛者的反響。文章涉及研究同性愛的若干理論和方法論問題。 Homosexuality exists in all times, all countries, all ethnic groups and all social classes. A survey shows that 2% of married men and women have homosexual experiences. It is a controversial issue on what causes a human being to be a homosexual. Many traditional behaviourists claims that homosexuality is a result of going astray in the course of growth and development. Although homosexuality has been excluded from mental illness by psychologists, but the public including a part of homosexuals themselves still think homosexuality perverse. But the majority of homosexuality maintain that homosexuality is not a choice, nor a disease, but a personal identity. The biological study on homosexuality began in the 18th century. In 1989 psychiatrists concluded that personal life in various aspects is determined by biological, familial, social and cultural factors of various kinds, sex orientation is a part of personal life, homosexuality is formed by more than one factor. But the dispute on nature v. nurture on homosexuality is still not solved: whether homosexuality is determined by environment or genetics. The findings of biological studies on homosexuality, especially on the correlation between homosexuality and brain structure in 1990s seem to s how that homosexuality is determined by genetic factor or at least influenced by this factor. But it cannot be ignored that the environment and psychological dynamics mechanism play a certain role in it. However, these findings caused further controversy. People with different sex orientation seem to make different interpretation of these findings. Somebody worries about that if homosexual gene is identified one day, this gene will be corrected by gene therapy, or the fetus with this gene will be aborted. Anyway, homosexuality is not simply preprogrammed, but a complex embodiment of one’s value and personality. Gene is a only part of it, but not its whole. DOWNLOAD HISTORY | This article has been downloaded 30 times in Digital Commons before migrating into this platform.